Attachment styles and healthcare utilization: exploring the role of the patient-doctor relationship - I. Schmalbach; G. H. Franke; W. Häuser; B. Strauss; K. Petrowski; Elmar Brähler (BMC, 2024)
Abstract Background With the purpose of improving healthcare, past research has examined the link between healthcare utilization and attachment. It is suggested that an individual's attachment style influences both the quality of their patient-physician relationship and healthcare utilization patterns. Nevertheless, most studies concentrate on the individual aspect, overlooking the dyadic dimension; specifically, the investigation of how insecure attachment relates to health behavior within patient-physician relationships. This gap leaves the role of the patient-doctor relationship in this process unclear. Therefore, to elucidate this complex interplay, we hypothesized that the correlation between attachment and healthcare utilization is mediated by the quality of the patient-physician-relationship. Method Participant selection was based on electoral districts, a random-route procedure, and the Kish selection grid. The participants were visited by a trained interviewer who collected psychometric and sociodemographic information. Participants answered the Experiences in Close Relationships-Revised questionnaire (ECR-RD8) and the Patient-Doctor Relationship Questionnaire (PDRQ-9). Additionally, participants were asked about their healthcare utilization. The final sample consisted of N = 2.275 participants. Results In average the participants reported consulting their primary health care practitioner M(SD) = 4.44 (4.76) times in the past 12 months. Generally, the participants rated the quality of the relationship with their primary health care practitioner close to "totally appropriate" (M = 4.12 ± .69). The degree of insecure attachment manifested towards the lower extremity of the scale. The total effect of the mediation analyses was significant. Regardless, the indirect effect indicated a trend result with minimal effect sizes. Conclusion The findings of the current study bridged the gap between attachment styles and healthcare utilization. Nonetheless, our results suggested insufficient support for the mediating role of the primary care physician in the relationship between attachment style and healthcare utilization. Considering the characteristics of the sample, this outcome may not apply in a clinical context. However, further research is needed to shed light in the revealed trends and indicate implications.